A new imaging approach for in situ and ex situ inspections of conductive fiber–reinforced composites by magnetic induction tomography. (June 2014) - Renner, Axel; Marschner, Uwe; Fischer, Wolf-Joachim
Fiber-reinforced plastics for industrial applications face constantly increasing demands regarding efficiency, reliability, and economy. Furthermore, it was shown that fiber-reinforced plastics with tailored reinforcements are superior to metallic or monolithic materials. However, a trustworthy description of the load-specific failure behavior and damage evolution of composite structures can hardly be given, because these processes are very complex and are still not entirely understood. Among other things, several research groups have shown that material damages like fiber fracture, delamination, matrix cracking, or flaws can be discovered by analyzing the electrical properties of conductive composites, for example, carbon fiber–reinforced plastics. Furthermore, it was shown that this method could be used for structural health monitoring or nondestructive evaluation. Within this study, magnetic induction tomography, which is a new imaging approach, is introduced in the topic of nondestructive evaluation of carbon fiber–reinforced plastics. This non-contacting imaging method gains the inner spatial distribution of conductivity of a specimen and depicts material inhomogeneity, like damages, not only in two-dimensional images but also in three-dimensional images. Numerical and experimental investigations are presented, which give a first impression of the performance of this technique. It is demonstrated that magnetic induction tomography is a promising approach for nondestructive evaluation. Potentially, it can be used for fabrication quality control of conductive fiber–reinforced plastics and as a structural health monitoring system using an integrated or superficially applied magnetic induction tomography setup.